Teachers’ Creativity in Using Multimedia to Encourage Students Speaking Ability during Pandemic - Rofiudin, Rofiudin; Asshifa , Handini Laely; Molla, Nur Laila (LPPM Universitas Pancasakti Tegal, 2022)
During the Covid-19 pandemic, English teachers encountered considerable challenges as they were required to adapt to online learning while mastering digital technologies and developing appropriate instructional media. This study employed a descriptive qualitative case study design to examine teachers’ creativity in using multimedia to encourage students’ speaking ability during the pandemic. The participants consisted of eighteen English teachers from seven private junior high schools in Kota Tegal, Central Java, Indonesia, who completed a questionnaire. In addition, semi-structured interviews were conducted with three teachers and two students from two selected schools to obtain in-depth qualitative data. The findings indicate that teachers utilized a wide range of multimedia and digital platforms to support speaking instruction. Interactive conversation videos were the most frequently used multimedia, reported by 50% of the respondents. Google Meet emerged as the primary platform for synchronous speaking activities, with 88.9% of teachers using it regularly. Online quiz platforms, such as Quizzes and Edmodo, were also commonly employed (83.3%) to enhance student engagement, while digital learning platforms such as Ruang Guru, Zenius, and Quipper were recommended to support students’ independent learning (72.2%). Furthermore, the study reveals that teachers demonstrated creativity by combining multiple media and platforms, designing flexible speaking tasks, establishing clear classroom rules, and creating a supportive and enjoyable online learning atmosphere. Collaboration with parents was also identified as an important strategy to maintain students’ learning discipline at home. Overall, the findings highlight the essential role of teacher creativity in sustaining effective EFL speaking instruction during emergency remote teaching.